The impacts of self-expectation leadership and organizational commitment on hand hygiene behavior of medical staff based on the theory of implicit leadership - Wang, Qianning; Lai, Xiaoquan; Zheng, Feiyang; Yu, Tiantian; Wang, Lu; Wu, Yuanyang; Wang, Kang; Zhang, Xinping; Zhou, Qian; Tan, Li (Frontiers in Psychology, 2022)
Hand Hygiene Behavior (HHB) in health-care settings remains suboptimal globally. Self-expectation leadership and organizational commitment are emphasized as important factors influencing HHB. However, there are no studies to support any relationship between self-expectation leadership and organizational commitment with HHB. This study will fill the gap by applying implicit leadership theory (ILT) to support the further promote HHB among medical staff. A cross-sectional study of 23426 medical staff was conducted in all second-level and third-level hospitals in Hubei province, China. Based on ILT, an online self-administered and anonymous questionnaire was designed for measuring the medical staff's self-expectation leadership, organizational commitment and HHB based on Offermann's 8 dimensions scale, Chang's 3 dimensions scale and the specification of hand hygiene for healthcare workers respectively, in which self-expectation leadership was divided into positive traits and negative traits parts. Structural equation model was used to examine the direct, indirect and mediating effects of the variables. Positive traits of self-expectation leadership had a positive effect on organizational commitment (β = 0.617, p < 0.001) and HHB (β = 0.180, p < 0.001). Negative traits of self-expectation leadership had a negative effect on organizational commitment (β = -0.032, p < 0.001), while positive effect on HHB (β = 0.048, p < 0.001). Organizational commitment had a positive effect on HHB (β = 0.419, p < 0.001). The mediating effect of the organizational commitment showed positively between positive traits of self-expectation leadership and HHB (β = 0.259, p < 0.001), while negatively between negative traits of self-expectation leadership and HHB (β = -0.013, p < 0.001). Positive traits of self-expectation leadership are important predictors of promoting organizational commitment and HHB, while negative traits of self-expectation leadership have a limited impact on organizational commitment and HHB in the field of health-care associated infection prevention and control. These findings suggest the need to focus on positive traits of self-expectation leadership, although negative traits of self-expectation leadership can also promote HHB to a lesser degree among medical staff, it will reduce their organizational commitment.